Padang Halal Tourism: Studi Kasus Terhadap City Branding Pada Pusat Perdagangan Kota Padang - Fitri Adona; Yusnani Yusnani; Sukatik Sukatik (Jurnal Ilmiah Poli Bisnis, 2019)
Since West Sumatra established itself as the world's best halal tourist destination at the World Halal Tourism Award 2016, Padang City is automatically synonymous with the city of "Halal Tourism". The victory in the category of Worlds Best Halal Culinary Destination and World's Best Halal Destination motivated the Padang City Government and all stakeholders to build awareness that the time for tourism in the City of Padang was to rise up and be aligned with other regions in Indonesia. But the fundamental problem faced in the development of Padang City tourism is the non-specificity of the Padang City city branding with the cities and regencies in West Sumatra. Case studies reveal, that the pattern and concept of city branding halal tourism has not been created yet, there is no guarantee that Padang City holds the main principles and conditions for halal tourism even though the population is predominantly Muslim. Important factors for Muslim tourists may also be partly accommodated, such as halal labels, worship facilities and halal services. Padang must be more consistent in the selection of city branding and conducting socialization and promotion on an ongoing basis.